Ginger Post-Harvest Cleaning Machine by Spraying Pressurized Water - Rosales Uscuchagua, Jimmy (2024)
The following research work developed a post-harvest ginger washing machine to conserve and improve the quality of ginger in the province of Satipo. The harvest needs to go through a washing process to remove impurities and other residues, so the main objective of this research project was to design a ginger washing machine with an improved pressurized water system, with a horizontal drum that has turning paddles and a sample drawer for quality control, reusing the water by filtering it through a sand trap. This work was carried out by developing an adaptation of the VDI 2221 and VDI 2225 standards, resulting in 4 phases to develop the project: the first, gathering information; the second, defining the solution concept, which seeks the solution to the problem; the third, the development and design; and finally, the design/modeling of the machine using software to validate its operation. The results in the design phase determined that it should have a feeding hopper, a horizontal drum, which should handle a maximum production of 40 (kg/min), a small sample drawer at one end to check the quality of the ginger, a 4.5 hp motor reducer that is in charge of the shaft rotation drive; the recirculation and washing by means of constant pressure are handled by a 1⁄2 HP motor-pump which expels the water through an injector tube that has cuts in the shape of a cross.